PROBLEMS OF LEGAL CAPACITY IN AMENDING LOCAL ACTS OF HIGHER EDUCATION INSTITUTIONS - Bilyi, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: this study aims to examine the legitimacy of simplified procedures for amending collective agreements at higher education institutions (HEIs) in the absence of specific legal regulation and to substantiate the subsidiary application of general labor legislation norms. Methods: the research employs systematic analysis of legal norms, comparative legal analysis of European delegation practices, and analysis of local acts from leading Ukrainian HEIs. Results: the study establishes the absence of specific regulation regarding amendment procedures for collective agreements in educational legislation and identifies a legal lacuna filled through subsidiary application of Article 14 of the Law «On Collective Agreements and Accords». The research validates the legitimacy of simplified procedures established by HEI local acts and refutes the applicability of civil law norms due to the public law nature of collective agreements. Analysis of practices from leading Ukrainian universities demonstrates widespread use of differentiated amendment procedures through working commissions for minor or technical changes. Comparative analysis of international experience (Ireland, France, USA, Germany) confirms the legitimacy of delegation principles when formal requirements are met. Discussion: the findings substantiate the necessity of legislative regulation establishing criteria for distinguishing between substantial and non-substantial amendments to ensure legal certainty and develop social dialogue mechanisms in the educational sector. The study recommends: 1) legislative consolidation of criteria for categorizing amendments; 2) establishing mandatory elements for simplified procedures including written formalization of delegated authority; 3) developing methodological guidelines for HEIs on optimal models of internal regulation.